Cancer Profile in North Jakarta and Kepulauan Seribu : A 5-year descriptive study - Gondhowiardjo, Soehartati Argadikoesoema; Bramantyo, Dion Firli; Octavianus, Steven; Priharto, R Koesmedi; Yekti, Widyastuti Endro (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2018)
Background: Cancer is the leading causes of death with a comparable number of mortality rate to coronary heart disease and stroke. The burden of cancer will continue to increase, especially in developing countries including Indonesia. This study reports the profile of cancer patients domiciled in the administrative area of North Jakarta and Kepulauan Seribu in 2008 ? 2012.Materials and Methods: This was a descriptive study. Patients data were collected from cancer registries all hospitals located in administrative area of North Jakarta and Kepulauan Seribu. This data was pooled and extracted from DKI Jakarta Cancer Registry Control Center at RSCM. The primary site and histology of malignancies were verified and coded based on the International Classification of Diseases for Oncology (ICD-O). Data were analyzed using descriptive statistics in SPSS 20.0Results: There are 2185 cases or around 14.8% of all cases of cancer patients verified in the database. Of those, 740 were male and 1445 female. The most prevalent age group was 45 - 54 years old, which was 29%. The highest distribution of cancer stage was in stage 3, which is 21.1%. The most common cancer in all sex groups were breast cancer, cervical cancer, nasopharyngeal cancer, hematopoietic system malignancy, and ovarian cancer. In men, the top five most cancers were nasopharyngeal cancer, lung cancer, hematopoietic system, lymphoma, and liver cancer. Whereas in women, most cancer sequences were breast cancer, cervical cancer, ovarian cancer, thyroid cancer, and hematopoietic system.